Diversity and Distribution of Phaeophyta Macroalgae in Pedalen Coastal Waters, Kebumen - Dwi Sunu Widyartini; Achmad Ilalqisny Insan; Hexa Apriliana Hidayah (Jurnal Ilmu Pertanian Indonesia, 2023)
Pedalen Beach, Kebumen, has a type of water substrate consists of sand, coral fragments, and coral overgrown with macroalgae. This study aims to determine the species diversity and distribution pattern of Phaeophyta found in that waters. This research is to explore and utilize macroalgae as a sustainable alginate resource. This study uses a survey method, employing the line transect method randomly. The research variables were species diversity and the distribution pattern of Phaeophyta. The main parameters were the number of species and individuals of each species. Supporting parameters include current velocity, nitrate content, brightness, depth, tide, salinity, temperature, and pH. The data were analyzed using the Shannon-Wiener diversity index (H’) to determine the level of species diversity and the Morisita distribution index (Id) to describe the distribution pattern of macroalgae species. We found five Phaeophyta species consisting of Padina australis, Dictyota dichotoma, Turbinaria ornata, Sargassum crassifolium, and S. polycystum. The diversity of Phaeophyta is classified as low diversity index value (H’) with distribution patterns of uniform macroalgae species. The results of the measurement of physical and chemical factors of the waters showed that the condition of the Pedalen Beach waters was quite good for the growth of Phaeophyta. Keywords: alginate, macroalgae species, Phaeophyta, water substrate